Detecção e classificação de transitórios em redes de distribuição para identificação de faltas de alta impedância - Farias, Patrick Escalante (2013)
Protection systems used in distribution networks of electricity are not able to detect short circuits with high contact resistance due to the low currents generated, endangering the population and degrading the quality of the energy supplied. In this sense, this paper presents a new methodology for detecting high-impedance faults (HIF) in distribution networks. The developed algorithm has the main advantage the fact also detect and classify other types of transient as, for example, switching capacitor banks, transformers and loads. This characteristic decreases the improper operation caused by transient switching. Another feature of the developed method is no need to install additional equipment on the network which greatly reduces the cost of implementation. Additionally, the paper also discusses the causes, consequences and characteristics of HIF in order to evidence the difficulties related to their detection. A brief review of the models proposed in the literature for computational simulation of HIF is also discussed, and the model used in this work is described in detail. To evaluate the performance of the algorithm developed a series of tests with different fault scenarios high impedance were made. Furthermore, other various types of transients that are normal in the feeders were tested. The good results obtained, combined the simplicity of the method and does not need to install additional equipment feeders, makes a promising technique for real applications.